Green Synthesis of New Category of Pyrano[3,2-c]Chromene-Diones Catalyzed by Nanocomposite as Fe3O4@SiO2-Propyl Covalented Dapsone-Copper Complex - Zare Fekri, Leila (Frontiers in Chemistry, 2021)
Nanomagnetic dapsone-Cu supported on the silica-coated Fe3O4 (Fe3O4@SiO2-pr@dapsone-Cu) nanocomposite was synthesized and characterized by Fourier transform infrared (FT-IR), energy-dispersive X-ray (EDX), X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), transmission electron microscopy (TEM), zeta potential, vibrating sample magnetometer (VSM), and thermogravimetric analysis (TGA). This newly synthesized nanocomposite was chosen to act as a green, efficient, and recyclable Lewis acid for the multicomponent synthesis of new derivatives of pyrano[3,2-c]chromene-diones through the reaction of aromatic aldehydes, indandione, and 4-hydroxycoumarin in water. All of the synthesized compounds are new and are recognized by FT-IR, NMR, and elemental analysis; this avenue is new and has advantages such as short reaction times, high productivity, economical synthesis, and use of green solvent, H2O, as a medium. The catalyst is magnetically recoverable and can be used after six runs without a decrease in the efficiency.